2011
DOI: 10.1002/jmri.22681
|View full text |Cite
|
Sign up to set email alerts
|

First order correction for T2*‐relaxation in determining contrast agent concentration from spoiled gradient echo pulse sequence signal intensity

Abstract: Purpose: To investigate the accuracy of a method neglecting T 2 *-relaxation, for the conversion of spoiled gradient echo pulse sequence signal intensity to contrast agent (CA) concentration, in dynamic contrast enhanced MRI studies. In addition a new closed form conversion expression is proposed that accounts for a first order approximation of T 2 *-relaxation. Materials and Methods:The accuracy of both conversion methods is compared theoretically by means of simulations for four pulse sequences from literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The causes of inaccuracy in the AIF measurement have been thoroughly studied in the literature [6,8,16,17,38] and may be identified in many sources. Examples are the T 2 * saturation due to high contrast agent concentration in vessels, flow, or partial volume effects.…”
Section: Why χ Ma and Mb Can Be Wrong: Sources Of Error Resulting Inmentioning
confidence: 99%
See 3 more Smart Citations
“…The causes of inaccuracy in the AIF measurement have been thoroughly studied in the literature [6,8,16,17,38] and may be identified in many sources. Examples are the T 2 * saturation due to high contrast agent concentration in vessels, flow, or partial volume effects.…”
Section: Why χ Ma and Mb Can Be Wrong: Sources Of Error Resulting Inmentioning
confidence: 99%
“…Moreover, because of the high concentrations of CA in large vessels, where the plasma signal is sampled, the approximation of negligible T 2 * in Eq. (4) might not be valid [6]. It is therefore not possible to model errors on C p (t) in the same way errors are modeled in C t (t).…”
Section: 22mentioning
confidence: 94%
See 2 more Smart Citations
“…The underestimations were reduced by correction with T 2 * measurements. De Naeyer et al [21] also showed that neglecting T 2 * could lead to errors in arterial concentration estimation up to 43%. In contrast, the corresponding underestimation of the AIF in our study ranged from 6.2% to 37.1% with a mean of 21.3%, indicating that the T 2 * effect in reference muscle tissue may be smaller than in direct arterial measurements.…”
Section: Discussionmentioning
confidence: 99%